Subaponeurotic fluid collection (SFC) in an infant - Wong, KCS; Ahmad Khaldun Ismail,; Al Kuddoos NM, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Subaponeurotic fluid collection is an infrequent cause of scalp swelling in infants. We report a 10-week-old male who had a scalp swelling for five days without any recent history of head injury. There was a soft, mobile, non-tender, transilluminating, fluctuant swelling over posterior parieto-occipital area and it was not limited by suture lines. Cranial ultrasonography showed a subaponeurotic collection at the posterior parieto-occipital area without definite communication with the intracranial space or the brain parenchyma. This infant was treatedconservatively. The swelling resolved spontaneously after 4 weeks. The lack of awareness of some doctors in the Emergency Department about this condition may lead to unnecessary investigations, ward admission and intervention. It is hoped that this case report will provide emergency health care professionals the confidence to make accurate diagnosis and treat patient with subaponeurotic fluid collection optimally.